2019
DOI: 10.1002/mrm.28056
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging of mean cell size in human breast tumors

Abstract: Purpose Cell size is a fundamental characteristic of all tissues, and changes in cell size in cancer reflect tumor status and response to treatments, such as apoptosis and cell‐cycle arrest. Unfortunately, cell size can currently be obtained only by pathological evaluation of tumor tissue samples obtained invasively. Previous imaging approaches are limited to preclinical MRI scanners or require relatively long acquisition times that are impractical for clinical imaging. There is a need to develop cell‐size ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
97
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(103 citation statements)
references
References 48 publications
5
97
0
Order By: Relevance
“…50 Another assumption is having the same diffusivity inside and outside the sphere, with time-dependence originating only from restricted diffusion, which might once again lead to bias. 46,64 Nevertheless, this assumption has been successfully applied in the past to model various tumor types, 33,37,40 with fitted parameters showing a good correlation with histology features. 33,41 It is important to stress that, even if the estimated model parameters do not naturally correspond to features visible to histology, the modeling approach successfully captured the higher-order effects in the signal decay and recovered parameters, which were useful for lymph node classification, whereas the ADC approach was much less sensitive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…50 Another assumption is having the same diffusivity inside and outside the sphere, with time-dependence originating only from restricted diffusion, which might once again lead to bias. 46,64 Nevertheless, this assumption has been successfully applied in the past to model various tumor types, 33,37,40 with fitted parameters showing a good correlation with histology features. 33,41 It is important to stress that, even if the estimated model parameters do not naturally correspond to features visible to histology, the modeling approach successfully captured the higher-order effects in the signal decay and recovered parameters, which were useful for lymph node classification, whereas the ADC approach was much less sensitive.…”
Section: Discussionmentioning
confidence: 99%
“…To further enhance the specificity of dMRI-derived parameters to the underlying microstructure, recently proposed higher-order dMRI techniques [33][34][35][36][37][38][39][40] employ biophysical compartment models of various (assumed) tissue features to fit the dMRI measurements, usually acquired at multiple b-values and diffusion times. Such approaches showed enhanced ability over ADC to explain the diffusion measurements and differentiate between benign and malignant tumors in various cancer types such as xenograft colorectal tumors, 33 prostate cancer, 37,41-44 breast cancer, 40 and gliomas. 45,46 Moreover, the estimated dMRI parameters for restriction size and volume fraction correlated well with histology measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to previous studies, 12,14,16,23 MRI‐cytometry assumes diffusion MRI signals arise from 2 compartments, that is, intra‐ and extracellular spaces without transcytolemmal water exchange. The following assumptions were made.…”
Section: Theorymentioning
confidence: 82%
“…vd=πd3/6 is cell volume; Pitalicind,Ditalicin is the normalized distribution function of the number of cells with a diameter d and an intracellular diffusivity Din; PitalicexDex0,βitalicex is the normalized distribution function of the number of spin packets with Dex0 and βex; ρin and ρex are the T 2 ‐weighted intra‐ and extracellular diffusion MRI signals per unit volume, respectively; and sin is intracellular signal attenuation of an impermeable spherical cell. The analytical equations for sin linking geometric features ( d and Din) to diffusion MRI signals have been reported for sine‐ and cosine‐modulated gradient waveforms 27 and cosine‐modulated trapezoidal OGSE waveforms 23 . Unlike previous studies that enforced a known distribution function, 28 Equation () does not assume any specific distribution function for any microstructural parameters.…”
Section: Theorymentioning
confidence: 99%
“…This leads to a limited capacity to access shorter diffusion times, [24][25][26][27] as the effective diffusion time is approximately 1/4f. 8 Nevertheless, recent studies have investigated the feasibility and utility of OG-dMRI on clinical systems, [24][25][26][27][28][29][30][31][32][33][34][35] given the limited oscillating frequencies and b-values. For example, Xu et al 32 demonstrated that on a 3T clinical scanner, cell size could be accurately estimated in breast cancer with a simplified PG-dMRI and OG-dMRI protocol and an advanced biophysical model.…”
Section: Introductionmentioning
confidence: 99%